2020
DOI: 10.3390/ma13051138
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Failure Analysis of Thin-Walled Composite Structures Verified Experimentally

Abstract: The subject of the presented research was a thin-walled composite column made of CFRP (carbon-epoxy laminate). The test sample had a top-hat cross-section with a symmetrical arrangement of laminate layers [90/−45/45/0]s. The composite structure was subjected to the process of axial compression. Experimental and numerical tests for the loss of stability and load-carrying capacity of the composite construction were carried out. The numerical buckling analysis was carried out based on the minimum potential energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…This problem was raised, among others, in [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], where the authors showed that a structure with local buckling of its elements can still be used, provided that the mode of stability loss is elastic buckling and that the post-critical equilibrium path is stable. This observation has also been confirmed by the author’s previous studies [ 32 , 33 , 34 , 35 ] devoted to the loss of stability of compressed thin-walled composite profiles, the results of which have shown that, in spite of buckling, thin-walled profiles retain a considerable reserve of load-carrying capacity allowing for the safe bearing of loads in the post-critical range.…”
Section: Introductionsupporting
confidence: 80%
“…This problem was raised, among others, in [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], where the authors showed that a structure with local buckling of its elements can still be used, provided that the mode of stability loss is elastic buckling and that the post-critical equilibrium path is stable. This observation has also been confirmed by the author’s previous studies [ 32 , 33 , 34 , 35 ] devoted to the loss of stability of compressed thin-walled composite profiles, the results of which have shown that, in spite of buckling, thin-walled profiles retain a considerable reserve of load-carrying capacity allowing for the safe bearing of loads in the post-critical range.…”
Section: Introductionsupporting
confidence: 80%
“…The C-profile was made as a shell finite element with a defined thickness. The material model within the discrete model was prepared on the basis of information from experimental tests [ 9 ]. On the basis of the σ-ε relationship obtained in laboratory coupon test, the bilinear elastic–plastic material model with strain hardening was adopted in the FEM numerical model.…”
Section: Numerical Studymentioning
confidence: 99%
“…The laminated tape used for the face sheets was considered to be a thin and narrow plate. For the case of thin plates or shells, it is customary to use shell elements [ 21 , 22 , 23 , 24 ]. Furthermore, as the laminated sheets were produced as a one-layer tape, a single-layer shell element can be used.…”
Section: Methodsmentioning
confidence: 99%